2001
DOI: 10.1159/000046616
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenic Therapy in Leukemia

Abstract: Angiogenesis is a fundamental element of the physiological processes of embryogenesis and wound healing. During malignant transformation, dysregulation of angiogenesis leads to the formation of a vascular network of tumor-associated capillaries promoting survival and proliferation of the cancerous cells. Activation, migration, proliferation and differentiation of endothelial cells into mature blood vessels is driven by several cytokines and growth factors, known to be dysregulated in hematological malignancies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 85 publications
0
18
0
1
Order By: Relevance
“…The initial agent investigated in this context was thalidomide, which has both antiangiogenic and immunomodulatory properties (35,36). In all studies reported to date, varying rates and degrees of response to thalidomide have been documented, including in patients who have failed aggressive standard combination cytotoxic and corticosteroid therapy (37)(38)(39)(40).…”
Section: Introductionmentioning
confidence: 99%
“…The initial agent investigated in this context was thalidomide, which has both antiangiogenic and immunomodulatory properties (35,36). In all studies reported to date, varying rates and degrees of response to thalidomide have been documented, including in patients who have failed aggressive standard combination cytotoxic and corticosteroid therapy (37)(38)(39)(40).…”
Section: Introductionmentioning
confidence: 99%
“…33,34 It has been shown in several studies that systemic levels of these mediators could be important in the regulation of angiogenesis. 10,35,36 Most of the initial studies in angiogenesis were done on solid tumors. However, there are increasing numbers of studies that demonstrate the importance of angiogenesis in hematologic malignancies.…”
Section: 32mentioning
confidence: 99%
“…[7][8][9] Recently, it has also been recognized that disregulation of angiogenesis constitutes an important step in the development and progression of hematological malignancies and that leukemias may invade and proliferate in the bone marrow and other organs by mechanisms similar to those reported in solid tumors. 10 The interaction of endothelial cells and the marrow microenvironment with hematopoietic progenitors and leukemia cells play a role in the development of the leukemic phenotype by virtue of the secretion of proangiogenic and antiangiogenic cytokins. The blood levels of pro-angiogenic and anti-angiogenic growth factors can be measured and may have prognostic and diagnostic values.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a number of preclinical investigations that confirmed the pathophyiologic role of angiogenesis in leukemias and MDS, a number of small molecule inhibitors of angiogenic agents and receptors have been developed and have entered clinical trials. 74 Thalidomide. Thalidomide has significant antitumor activity in patients who have hematologic malignancies with increased bone marrow angiogenesis and has been shown to inhibit bFGF and VEGF-induced angiogenesis.…”
Section: Angiogenesis Inhibitorsmentioning
confidence: 99%